Towards realizing an ASEAN community a brief report on the ASEAN Community Roundtable (Institute of Southeast Asian Studies, 2004)
ASEAN has produced a plan of action on ASEAN Economic Integration, which is annexed to the Bali Concord II. To kick-start the ASEAN Economic Community (AEC), the plan of action provides numerous policy recommendations to be implemented over the next 1 to 2 years. At the track-two level, research institutes/think-tanks such as ASEAN-ISIS, ISEAS and CSIS (Jakarta) have contributed concept papers on the AEC and the ASEAN Security Community (ASC).Against this backdrop, the Institute of Southeast Asian Studies (ISEAS) organized the ASEAN Community Roundtable in Singapore from 4 to 5 June 2004. The main theme of the Roundtable was entitled "Towards Realizing an ASEAN Community".This Roundtable provided the opportunity for scholars and experts on ASEAN to "brain-storm" in a more comprehensive and integrated manner, the different ideas and proposals underpinning the process of community building that ASEAN is embarking upon. This report reflects the conclusions that emerged from the ASEAN Community Roundtable